Top management team incentive heterogeneity, strategic investment behavior, and performance: A contingency theory of incentive alignment - Steinbach, Adam L.; Holcomb, Tim R.; Holmes, R. Michael; Devers, Cynthia E.; Cannella, Albert A. (Strategic Management Journal, 2017)
Research summary : We develop and test a contingency theory of the influence of top management team ( TMT ) performance‐contingent incentives on manager–shareholder interest alignment. Our results support our theory by showing that although TMT s engage in significantly higher levels of acquisition investment when their average incentive levels increase, investors' responses to those large investments are generally negative. More importantly, however, we further find that within‐ TMT incentive heterogeneity conditions that effect, such that investors evaluate TMT s' large acquisition investments more positively as the variance in those top managers' incentive values increases. Thus, within‐ TMT incentive heterogeneity appears to increase manager–shareholder interest alignment, in the context of large acquisition investments . Managerial summary : We find that as the average value of TMT s' incentives increase, relative to their total pay, they invest more in acquisitions and investors' respond negatively to the announcement of those deals. However, we further show that investors respond more positively to acquisitions announced by TMT s whose members' incentive values vary (some TMT members hold higher incentives and others hold lower). Results imply that when TMT members hold differing incentives levels, they approach investments from divergent perspectives, scrutinize those investments more heavily, and make better decisions, relative to TMT s with similar incentives. They also suggest that boards seeking tighter manager–shareholder interest alignment may benefit from introducing variance into TMT members' incentive structures, as doing so appears to create divergent preferences that can improve team decision making . Copyright © 2016 John Wiley & Sons, Ltd.